ANALISIS PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH ASURANSI (Studi Kasus Pada PT. Allianz Life Cabang Pangkalpinang) - Oktari, Indah; Prima Nugroho, Stefanus; Hariyani (Jurnal Progresif Manajemen Bisnis, 2018)
The purpose of this study is to examine the analysis of influence of Service Quality and Product Quality Against Customer Satisfaction Insurance at PT. Allianz Life Branch Pangkalpinang. The population in this study is all insurance customers of PT. Allianz Life Branch Pangkalpinang 2015 to 2017 which amounted to 887 customers. The sample in this study used the Probability Sampling method with a simple random sampling technique, with a number of respondents 90 respondents. The variables used are Quality of Service and Product Quality as the independent variable and Customer Satisfaction as the dependent variable, which is developed according to its own indicators. This research uses technical qualitative data analysis and quantitative data analysis of direct field results data, as a tool for processing statistical data using the SPSS program. The results showed that the Quality of Service and Product Quality positively and significantly affect customer satisfaction, simultaneously obtaining the value of Fcount (29,889)> Ftable (3.10) which means H1 accepted. Partially, Service Quality gives a significant influence to Customer Satisfaction with tcount value (4,948)> ttable (1,98729) which means H1 accepted. Product Quality has a significant effect on Customer Satisfaction with the acquisition of tcount (5.056)> ttable (1.98729) which means H1 accepted. That the coefficient of determination (r2) 74.6% means the effect of Quality Service and Product Quality together have a positive and significant impact on customer satisfaction, the remaining 25.4% influenced by other variables not included in this study. Based on the results of these studies, the researchers concluded that the satisfaction of insurance customers PT. Allianz Life Branch Pangkalpinang can be improved through service quality and product quality.